Chapter 1 Media and translation Historical intersections - O'Connor, Anne (Taylor & Francis, 2022)
This chapter examines how the intersections between media and translation have been theorized and highlights medial interactions with forms and processes of translation. In so doing, it discusses the impact of media and translation on each other; the significance of the non-human agent in the production, circulation and reception of translations; and the levels of agency attributed to media. The chapter considers how the media of composition and the media of transmission might have a bearing on the eventual form and impact of the translation product, and discusses the growing calls for media technologies to be seen as constitutive in meaning making, rather than mere containers. Using three diverse historical examples, the chapter traces moments of intersection between media and translation, posing questions on how materiality, technicity, mediality and translation can be perceived to interact and engage with each other.